A molecular dynamics study of the effect of nanoparticles coating on thermal conductivity of nanofluids. (20th January 2021) - Roni, Md. Rakibul Hasan; Shahadat, Muhammad Rubayat Bin; Morshed, A.K.M. Monjur Monjur
Abstract: Nanofluids have become the subject of theoretical and experimental researches over the last few decades due to their enhanced heat transfer performance. In this study, thermal conductivity of copper argon nanofluids containing coated and non‐coated copper particles is determined through MD simulation. Coating over the nanoparticles is applied to provide long‐term stable dispersion and also to enhance the heat transfer performance. Thermal conductivity of nanofluids depends on the types of coating applied over the nanoparticles. The role of surface coating over the nanoparticles in enhancing thermal properties of the nanofluids is discussed and compared to that of non‐coated particles. The silver coating is applied over the copper nanoparticles. Green Kubo method is employed to determine the thermal conductivity of the nanofluids. Result shows that, for volume fraction 3% and 86 K system temperature, thermal conductivity enhancement of nanofluid containing coated particle is 17% compared to that of base fluid and without coating, thermal conductivity enhancement is 12%. The mechanism of increased heat transfer performance for surface coating over the nanoparticles is discussed in this paper.